2014
DOI: 10.1186/1472-6920-14-223
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between medical student learning opportunities and preparedness for practice: a questionnaire study

Abstract: BackgroundAlongside providing a knowledge base and practical skills, undergraduate medical education must prepare graduates to immediately begin practice as qualified doctors. A significant challenge is to provide safe learning opportunities that will optimise students’ preparedness to start work. This study examined UK graduates’ preparedness for clinical practice, and their exposure to real-life and simulated immediate care scenarios during final year placements.MethodA questionnaire measuring students’ perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 28 publications
7
66
0
1
Order By: Relevance
“…This study was conducted at a time of increasing national 9 and international 1 , 3 , 15 17 focus on the preparedness of medical graduates for practice. The General Medical Council (UK) has systematically examined the question over the past decade, and recently reported that one in ten graduates felt poorly prepared for entering medical practice 1 , 18 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study was conducted at a time of increasing national 9 and international 1 , 3 , 15 17 focus on the preparedness of medical graduates for practice. The General Medical Council (UK) has systematically examined the question over the past decade, and recently reported that one in ten graduates felt poorly prepared for entering medical practice 1 , 18 .…”
Section: Discussionmentioning
confidence: 99%
“…This study is also limited by its being a single site study in a regional university with small graduate numbers, meaning that its results may not be generalisable to other medical schools. Respondents' interpretation of what constitutes preparedness for each item may also have varied, given that there were no objective criteria for graduates to benchmark their own preparedness 1 , 15 . The judgements of graduates cannot be assumed to be equivalent, although it is likely that each graduate applied similar judgements to each of the 44 items.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This survey instrument was developed by the lead researcher, with the items based on previous surveys in the published literature, including a cross-sectional survey about the use of chiropractic technique pediatric patients 10 as well as surveys of preparedness for practice in medical students. 11,12 The pre-and postplacement surveys on preparedness were from those developed by the lead author for a retrospective survey of 275 chiropractic students across 4 chiropractic institutions. 13 This survey content was verified via an expert panel of pediatric chiropractors and then pilot tested on 3 newly graduated chiropractic students for clarity.…”
Section: Methodsmentioning
confidence: 99%
“…Scholars across many disciplines have examined the affordances of student learning in the context of the environment in which they eventually practice as a professional. There is evidence that work related learning has a positive influence on student learning outcomes, and their readiness for work or preparedness for practice (Warren 2012;Burford et al 2014;Morrow et al 2012;Svirko et al 2014). Medical students' preparedness for practice as junior doctors can be improved by prior experiential, work-based learning in clinical practice during their medical programme (Brennan et al 2010).…”
Section: Theoretical Frameworkmentioning
confidence: 99%